VERBAL AND NON-VERBAL SIGNS IN FACIAL WASH ADVERTISEMENTS: A SEMIOTIC ANALYSIS - Ria Andriani; I Dewa Ayu Devi Maharani Santika (Yavana Bhasha : Journal of English Language Education, 2021)
This study involves the discovery of verbal and non-verbal signs, which also describe themeaning of verbal and non-verbal signs found in the facial wash commercial advertisements. The datawere taken from three printed facial wash advertisements. The data source has been taken from theinternet. This study used the semiotic hypothesis provided by Saussure (1983: 65) to find out theverbal and non-verbal signs and the theoretical meaning provided by Barthes (1977) to find out themeaning of verbal and non-verbal signs in the facial wash ads. The analysis used a descriptivequalitative approach to analyze the results. As a result, the three facial wash ads show verbal and nonverbalsigns that enable the company to market its product. In the verbal signs of the advertising, mostof them contain denotative meaning and non-verbal signs which is in part, contain connotativemeaning in certain advertisements. Two advertisements used a female as a model; one advertisementused a male as a model. This means that advertisers seek to gain public attention through the use ofpretty females, popular figures and natural extracts or ingredients.